Comparison between automated DNA extraction employing the EZ1 platform and manual methods using real forensic samples - FRANCEZ, PABLO ABDON DA COSTA; PENIDO, CIRO AUGUSTO FERNANDES DE OLIVEIRA; COSTA, GILCELENE DO SOCORRO MEDEIROS DE BRITO; DE ALMEIDA, RODRIGO MATOS; PENA, EDUARDA EMANUELLE SILVA; FUNABASHI, KARINA; RESQUE, RAFAEL LIMA (Revista Brasileira de Criminalística, 2021)
In the last 30 years, advances in Molecular Biology techniques have allowed its application as an essential tool in the criminal investigation, with a particularly relevant application in the determination of authorship of crimes and the identification of missing persons and unknown corpses. However, with the popularization of Forensic Genetics and the growth of violence, there has been a significant increase in the demand for these tests, which has led Forensic Genetics Laboratories to search for more efficient and safe methods of processing this increasing volume of samples. In this sense, automation was one of the adopted solutions, allowing the processing of the samples more accurately and with the minimum of human interference, reducing the risks, and being a more economical alternative when used in large scale. This paper aims to present the results obtained concerning the standardization of the use of an automated DNA extraction platform and to evaluate the advantages of this method in relation to the manual methods in the extraction of forensic samples from the Laboratory of Forensic Genetics of POLITEC-AP. For the realization of the experiments, 500 samples of DNA were extracted using manual methods (Organic and Chelex 100®) and using the automated extraction equipment EZ1 Advanced XL® from Qiagen ©. The automated extraction using the EZ1® following the manufacturer's protocol or after the adaptation of the protocol presented qualitative and quantitative results superior to those obtained using manual methods, both for reference saliva samples and unknown samples of unknown cadavers (teeth and bones) and secretions collected from victims of sexual violence.